2022
DOI: 10.1590/1519-6984.244703
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of petroleum by bacteria isolated from fishes of Indian Ocean

Abstract: In this study, oil degrading bacteria discovered from fish living near the oil ports at Karachi in Pakistan were characterized. The bacteria isolated from skin, gills, and gut in fish could consume crude oil as a source of carbon and energy. Total 36 isolates were tested using Nutrient Agar (NA) and MSA media with different crude oil concentrations (0.2%, 0.5%, 0.7%, 1%, 2%, and 5%) and 4 out of 36 isolates (two Gram positive and two Gram negative bacteria) were selected for further identification. 16S rRNA ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Pseudomonas and bacillus species not only efficient engine oil degraders, but also have been used to degrade crude oil and various petroleum fractions such as diesel [21,22,27]. [28] screened 36 isolates for their ability to degrade used engine oil and concluded that only four isolates: Pseudomonas azotoforman, Bacillus velezensis, Pseudomonas brenneri and Bacillus flexus, have better potential. Similarly, [29] tested the capacity of 5 isolates including Pseudomonas sp., Bacillus sp., Corynebacterium sp., Aeromonas sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudomonas and bacillus species not only efficient engine oil degraders, but also have been used to degrade crude oil and various petroleum fractions such as diesel [21,22,27]. [28] screened 36 isolates for their ability to degrade used engine oil and concluded that only four isolates: Pseudomonas azotoforman, Bacillus velezensis, Pseudomonas brenneri and Bacillus flexus, have better potential. Similarly, [29] tested the capacity of 5 isolates including Pseudomonas sp., Bacillus sp., Corynebacterium sp., Aeromonas sp.…”
Section: Resultsmentioning
confidence: 99%
“…The authors found that all the isolates degraded about 80% of each concentration. [28] screened Pseudomonas azotoforman, Bacillus velezensis, Pseudomonas brenneri and Bacillus flexus, for their ability to degrade used engine oil on nutrient agar and MSA agar containing 0.2-5% crude oil concentrations. They discovered that out of 42 engine oil components amended in the degradation medium, 26 were completely degraded by the isolates using GC-MS technique.…”
Section: Resultsmentioning
confidence: 99%
“…The fish industry of Pakistan is in progress, despite fish being cultivated in various culture conditions around the country. In fact, limited studies reported the vast bacterial flora that would render the population of culturable fish species around this country (Kousar et al, 2019;Ullah et al, 2021). Previously, we isolated characterized several bacteria from naturally infected farmed fish of Khyber Pakhtunkhwa (Ali et al, 2023) and marine species at Karachi Seaport (Ullah et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, limited studies reported the vast bacterial flora that would render the population of culturable fish species around this country (Kousar et al, 2019;Ullah et al, 2021). Previously, we isolated characterized several bacteria from naturally infected farmed fish of Khyber Pakhtunkhwa (Ali et al, 2023) and marine species at Karachi Seaport (Ullah et al, 2021). The scenario of co-existence of bacteria and fish EM that has immunological role against pathogenic bacteria (Bhatnagar et al, 2023;Flores-Kossack et al, 2020;Rauta et al, 2012;Saleh et al, 2018) compelled us to study the immunological role of EM from freshwater fish species in the divers aquatic environment of Pakistan.…”
Section: Discussionmentioning
confidence: 99%